Cutaneous adverse effects of the available COVID-19 vaccines - Bogdanov, Georgi (Clin Dermatol, 2021)
Vaccination has played a crucial role in the improvement of global health. Some of the world’s deadliest diseases, like smallpox and rinderpest, have been eradicated with the help of vaccines, and many others have been restrained. The appearance of the strain of coronavirus disease 2019 (COVID-19) severe acute respiratory syndrome coronavirus 2 and its impact on global health have made the development of effective and safe vaccines crucial for this new lethal disease. So far, there are three main types of COVID-19 vaccines in use around the world: messenger RNA–based vaccines, adenoviral vector vaccines, and inactivated whole-virus vaccines. Some of them have passed through phase 3 of safety and efficacy trials and are widely used for prophylaxis of COVID-19 infection. A plethora of cutaneous adverse events have been reported, most of them mild or moderate injection-site reactions. Some rare delayed inflammatory reactions such as “COVID arm” have also been reported, posing questions on their pathophysiology and clinical importance. Some rare serious adverse events, such as vaccine-induced prothrombotic immune thrombocytopenia and anaphylaxis, have been described raising great concerns on the safety of some widely spread vaccines. More data need to be collected with further and more detailed analysis. The overall risk of such severe adverse reactions remains extremely low, and the benefits of the existing vaccines in combating the widespread threat of COVID-19 continue to outweigh the risk of their side effects.